Microscopic origin of graphene nanosheets derived from coal-tar pitch by treating Al4C3 as the intermediate. Issue 21 (25th May 2021) - Lin, Peng; Zhang, Yinggan; Tan, Xiaolin; Xiong, Rui; Sa, Baisheng; Lin, Qilang
Abstract : The synthesis process of GNs from coal-tar pitch by treating Al4 C3 as the pyrolyzed precursor from both experimental and theoretical points of view. Abstract : The development of environmentally friendly, simple process and low cost synthesis methods for preparing graphene nanosheets (GNs) has attracted global interest. In this work, a simple and efficient method to synthesize GNs deriving from coal-tar pitch has been proposed from both experimental and theoretical point of views. The XRD, TEM and Raman results demonstrate that precursor Al4 C3 could provide a growth environment for the final product of GNs. Innovatively, we have unraveled the microscopic origin for the decomposition of Al4 C3 based on density functional theory calculations. It is highlighted that the surface energies and the analysis of elastic constants indicate the fact that the chemical etching process in Al4 C3 can happen, which is similar to the exfoliation of well-known transition metal carbides MXenes. Furthermore, different bond breaking mechanisms have been found in Al4 C3 at applied tensile and shear strains from the electron localization functions and stress–strain results. Our study not only offers an efficient method to synthesize GNs, but also to unravel the microscopic mechanism of fabrication by theoretical calculations.